IMPLEMENTASI METODE RESITASI DALAM PEMBELAJARAN DI MADRASAH IBTIDAIYAH NEGERI 2 JEMBER - mislikhah, st (Pendidikan Islam Pascasarjana IAIN Jember, 2018)
The purpose of this study is to describe the implementation of the recitation method in learning in the State Madrasah Ibtidaiyah (MIN) 2 Jember which includes the assignment phase, the phase of task implementation, and the phase of responsibility of the task. This study uses a qualitative descriptive approach. To obtain data in this study used observation, interview, and documentation techniques. The collected data was analyzed using a spiral analysis model proposed by Creswell. The results of this study are (1) In the assignment phase, the teacher gives the task clearly and precisely so that the child understands what is assigned, the assignment is given according to the abilities of students, there are instructions and resources that can help the work of students, and provided time enough to do the task. (2) In the implementation phase of this task, the teacher controls the implementation of the task so that the task can be done well and done by the students themselves if it is not done by someone else. the teacher is very instrumental in conducting guidance and supervision because with the guidance and supervision of the teacher the students will do the task seriously. (3) In this task responsibility phase students report the results of their work both verbally and in writing from the assignment given by the teacher. In reporting the results of his work this can be done individually or in groups, depending on the type of assignment given.